Brain-derived neurotrophic factor contributes to neurogenesis after intracerebral hemorrhage: a rodent model and human study - Lin, Ting-Chun; Tsai, Yi-Chieh; Chen, Yun-An; Young, Tai-Horng; Wu, Chung-Che; Chiang, Yung-Hsiao; Kao, Chia-Hsin; Huang, Abel Po-Hao; Hsu, Yi-Hua; Chen, Kai-Yun; Tsai, Li-Kai (Frontiers in Cellular Neuroscience, 2023)
Background and Purpose: Intracerebral hemorrhage (ICH) enhances neurogenesis in the subventricular zone (SVZ); however, the mechanism is not fully understood. We investigated the role of brain-derived neurotrophic factor (BDNF) in post-ICH neurogenesis in a rodent model and in patients with ICH using cerebrospinal fluid (CSF). Methods: A rat model of ICH was constructed via stereotaxic injection of collagenase into the left striatum. Patients with ICH receiving an external ventricular drain were prospectively enrolled. CSF was collected from rats and patients at different post-ICH times. Primary cultured rat neural stem cells (NSCs) were treated with CSF with or without BDNF-neutralized antibody. Immunohistochemistry and immunocytochemistry were used to detect NSC proliferation and differentiation. The BDNF concentration in CSF was quantified using enzyme-linked immunosorbent assays (ELISA). Results: In the rat model of ICH, the percentage of proliferating NSCs and neuroblasts in SVZ was elevated in bilateral hemispheres. The cultured rat NSCs treated with CSF from both rats and patients showed an increased capacity for proliferation and differentiation toward neuroblasts. BDNF concentration was higher in CSF collected from rats and patients with ICH than in controls. Blocking BDNF decreased the above-noted promotion of proliferation and differentiation of cultured NSCs by CSF treatment. In patients with ICH, the BDNF concentration in CSF and the neurogenesis-promoting capacity of post-ICH CSF correlated positively with ICH volume. Conclusion: BDNF in CSF contributes to post-ICH neurogenesis, including NSC proliferation and differentiation toward neuroblasts in a rat model and patients with ICH.